Sustainable Research Culture for Enhancing the Quality of Deliverables in Classroom Teaching-Learning Environment : An In-Depth Analysis - Choudhury, D. K. (Prabandhan: Indian Journal of Management, 2016)
In higher and technical education institutions across the globe, teaching and research complement and supplement each other, which leads to enhanced quality of deliverables in classrooms and constitutes a chain on the pattern of the supply chain in industry. Each and every component of the chain is linked and integrated with each other in such a fashion that it becomes unreasonable to think about any of the components without considering the importance of others. Naturally, the faculty inherits an institutional culture, whatsoever it may be, and often contributes to enrich and strengthen the existing culture or else create a new culture, which is more coherent with the short and long-term objectives of an institution. However, in the absence of an institution’s culture, the faculty try to develop a particular culture required for fulfilling the set objectives and ultimate goals of the institution. In the backdrop of the prevailing teaching and learning scenario in the country, what sort of research culture is expected to prevail in an institution has been studied in detail in different interfacing contexts. The present study is, therefore, a modest attempt to analyze how the research culture can be created in an academic institution not only for enhancing, but also for sustaining the quality of deliverables through effective classroom teaching-learning environment supported by proactive involvement and participation of students in such endeavours.